Envisioning energy futures in the North Atlantic oil industry: Avoidance, persistence, and transformation as responses to climate change. (November 2020) - Stoddart, Mark C.J.; McCurdy, Patrick; Slawinski, Natalie; Collins, Cory G.
Highlights: The North Atlantic oil sector demonstrates a range of energy future orientations. Avoidance, persistence, and transformation are key orientations to climate change. Movement towards low-carbon futures is emerging in unlikely places. The 2015 Paris Climate Change agreement has uneven impacts as a critical event. Social science research and perspectives are vital to understanding energy futures. Abstract: The oil industry is a focal point in discussions of climate change. However, environmental social science tends to view the oil sector as homogeneous in relation to climate change and energy futures. In this context, we ask: What is the range of energy futures that are envisioned and articulated through oil industry events in different operating regions? How do the energy futures articulated within oil industry events relate to issues of climate change and decarbonization? We use an event ethnography approach to analyse oil industry events in St. John's, Canada; Stavanger, Norway; and Aberdeen, Scotland. Here we show diverse orientations to climate change and energy futures, which we categorize as avoidance, persistence, and transformation. Energy futures research on energy and climate change often lacks engagement with social scientific perspectives. Our analysis sets out a framework for expanding the contribution of social science research on climate change and energy systems.